Heat Stroke with Status Epilepticus Secondary to Posterior Reversible Encephalopathy Syndrome (PRES) - Y. H. Koh (Case Reports in Critical Care)
Heat stroke is a life threatening, multisystem disorder characterized by severe hyperthermia (core body temperature > 41.1°C) with central nervous system dysfunction and/or other end organ damage. Neurological complications, such as disturbances of consciousness, convulsion, profound mental change, disorientation, or even prolonged coma, were present in almost all cases of exertional heat stroke (EHS). We present a case of EHS with severe rhabdomyolysis and acute oliguric kidney injury in a 20-year-old healthy marathon runner, who developed status epilepticus on Day 4 of his admission. The patient was managed in ICU with renal replacement therapy and aggressive seizure control. He made a full recovery after 2 weeks of ICU stay. Diagnosis of EHS with posterior reversible encephalopathy syndrome (PRES) secondary to acute kidney injury was made.